Development of Smart Air Pollution Monitoring System Using LoRa Technology - Sarnin, Suzi Seroja; Saipul, Nur Shahirah; Md Tan, Mohd Nor; Dohad, Mohd Rizal; Mohamad Yusof, Yuslinda Wati; S. Abdul Kadir, Ros Shilawani (Journal of Advanced Research Design, 2025)
The presence of elevated air pollution levels can lead to respiratory problems and certain cardiovascular conditions among individuals in the surrounding areas. Unfortunately, Malaysia currently lacks an air pollution monitoring system capable of promptly notifying the appropriate authorities. In such instances, it becomes impossible to take preventive measures before the pollution intensifies, exposing people to harmful levels of air pollution. With the current technological advancements, implementing an Internet of Things (IoT) system for monitoring air pollution and alerting authorities is the most effective way to ensure citizens live in a healthy environment. This paper aims to develop a smart air pollution monitoring system capable of detecting levels of Carbon Monoxide (CO), Carbon Dioxide (CO2), and smoke. The system will send a warning notification to the relevant authorities when gas concentrations reach predefined levels. The microcontroller will receive sensor data, undergo necessary processing, and transmit the information to Blynk’s cloud using LoRa technology. Simultaneously, the system will automatically store backup data on Google Sheets. Additionally, a notification for Carbon Dioxide (CO2) gas levels will be sent every hour while for Carbon Monoxide (CO) and smoke index, an alert will be triggered when the air pollution level surpasses a moderate range of Air Pollution Index (API) and displaying the current air pollution index. By developing this technology, we aim to measure air pollution based on Malaysia’s Air Pollution Index (API) and facilitate easier monitoring by authorities. The system will categorize pollution levels as unhealthy (API 101-200 PPM), very unhealthy (API 201-300 PPM), and beyond. This initiative will raise awareness among relevant authorities about the adverse effects of air pollution on health and prompt timely interventions.